Geo-Environmental Approaches for the Analysis and Assessment of Groundwater Resources at Catchment-Scale - Tziritis, Evangelos; Panagopoulos, Andreas (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on the tools and methods used for tackling the complexity of the different hydrological and hydrogeological set-ups, the hydrodynamic patterns, the site specifications, and the wide variability of internal and external factors and/or processes on the catchment-scale level that impose the need for combined integrated approaches of robust methods. This Special Issue aims to provide successful applications or new insights on the stand-alone or joint considerations of groundwater resources assessment and characterization methods and explore new state-of-the-art methodological concepts in light of a rapidly changing environment.